The PanCareFollowUp Care Intervention: A European harmonised approach to person-centred guideline-based survivorship care after childhood, adolescent and young adult cancer. (February 2022) - van Kalsbeek, Rebecca J.; Mulder, Renée L.; Haupt, Riccardo; Muraca, Monica; Hjorth, Lars; Follin, Cecilia; Kepak, Tomas; Kepakova, Katerina; Uyttebroeck, Anne; Mangelschots, Marlies; Falck Winther, Jeanette; Loonen, Jacqueline J.; et al.
Abstract: Background: Long-term follow-up (LTFU) care, although endorsed, is not available for the majority of adult survivors of childhood, adolescence and young adult (CAYA) cancer. Barriers to implementation include lack of time, knowledge, personnel and funding. Sustainable solutions are urgently needed to address the needs of CAYA cancer survivors to improve the quality of life and reduce the burden of late effects on survivors, health care systems and society. The European Union–funded PanCareFollowUp project, initiated by the Pan-European Network for Care of Survivors after Childhood and Adolescent Cancer, was established to facilitate the implementation of person-centred survivorship care across Europe. Patients and methods: The PanCareFollowUp Care Intervention was co-developed with survivors as part of the PanCareFollowUp project . It is a person-centred approach to survivorship care, supported by guidelines and with flexibility to adapt to local health care settings. The Care Intervention consists of three steps: (1) previsit completion of a Survivor Questionnaire (by the survivor) and Treatment Summary (by the health care provider [HCP]), (2) a clinic visit including shared decision-making, and (3) a follow-up call to finalise the individualised Survivorship Care Plan. Results: We developed the key components of the PanCareFollowUp Care Intervention : a PanCareFollowUp Survivor Questionnaire, Treatment Summary template, Survivorship Care Plan template, and educational materials for HCPs and survivors. Wide implementation of the PanCareFollowUp Care Intervention will be supported with a freely distributed Replication Manual on completion of the PanCareFollowUp project. Conclusions: The PanCareFollowUp Care Intervention will support the implementation of person-centred, guideline-based LTFU care in different health care settings across Europe to improve survivors' health and well-being. Highlights: Long-term follow-up care is essential for the health of childhood cancer survivors. PanCareFollowUp Care Intervention is suitable for all health care systems. Treatment summary, Survivorship Care Plan, recommendations and health information. Evaluation of feasibility and effectiveness of Care Intervention in four European countries. Replication manual for implementation at institutions will be available postproject.